The impact of social approval and respect model criteria on social relations - Rezaei, Zahra; Sadeghi, Ahmad; Bakhshi, Hamed (Social Determinants of Health, 2023)
Background: Social relations are a complex process and originate from the interaction of a person with the environment. People have an inherent need to establish social relations to have the approval and respect of the others. The current study was conducted to design a model of approval and respect in the social relations of the people of Quchan. Methods: The research philosophy was in the realm of pragmatism and the research method was mixed. Also, the research strategy in the qualitative part was foundational data theorizing, and in the quantitative part, the survey. To analyze the data of this research, in the qualitative part, MAXQDA software was used, and in the quantitative part, SPSS software (version 22) and PLS software were used. Results: The results obtained from the analysis of qualitative data show that the model of approval and respect in the social relations of the people of Quchan includes 19 open codes, of which 5 codes are related to the category of causal factors, 2 codes are related to the central category, 2 codes related to the strategy category, 4 codes related to the consequences category, 3 codes related to the context category, and 3 codes related to the intervention category. Also, in the quantitative part, the results of the data showed that the mentioned model has the required validity. Conclusion: It can be concluded that social relations imply desirable learned behaviors that enable people to have effective relationships with others and avoid unreasonable social reactions.